2019
DOI: 10.4103/jos.jos_72_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral environment and prescribed fluoride mouthwashes on different types of TMA wires – An in-vivo study

Abstract: OBJECTIVE: The aim of this study was to investigate the effect of intraoral conditions and fluoride mouthwashes on mechanical properties and surface characteristics of different types of titanium molybdenum alloy (TMA) wires. MATERIALS AND METHODS: Three types of TMA wires of dimension 0.017” × 0.025” [1. Standard TMA (TMA), 2. ion-implanted, low-friction TMA (LF) and 3. Colored, Honey Dew TMA (HD)] were tested in three conditions as three groups; A) Control (as receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Previous studies on orthodontic wires have shown deterioration of both mechanical and physical properties after being subjected to an acidic environment [16][17][18][19][20]. Baidas et al (2020) evaluated the surface roughness and frictional resistance of orthodontic archwires in simulated gastric acid and concluded that the surface roughness of beta-titanium and stainless-steel archwires was signi cantly affected when subjected to acidic conditions [16].…”
Section: Denicola Et Al (mentioning
confidence: 99%
“…Previous studies on orthodontic wires have shown deterioration of both mechanical and physical properties after being subjected to an acidic environment [16][17][18][19][20]. Baidas et al (2020) evaluated the surface roughness and frictional resistance of orthodontic archwires in simulated gastric acid and concluded that the surface roughness of beta-titanium and stainless-steel archwires was signi cantly affected when subjected to acidic conditions [16].…”
Section: Denicola Et Al (mentioning
confidence: 99%
“…The downside of using these fluorides is the increased corrosion susceptibility of metallic alloys [29,42,264,[276][277][278][279][280][281][282]. Fluoride ions (F − )-combined with mechanical brushing-easily degrade the protective oxide layers of both SS and Ti-based alloys (see Equations ( 8) and ( 9)), increasing localized and general corrosion, promoting metallic ions release [276,283], and negatively impacting their mechanical and surface properties [41,42,277,279,282,[284][285][286]]-especially at low pH [104,118] and under the simultaneous presence of chloride ions [287].…”
Section: Oral Hygiene With Fluoride-based Productsmentioning
confidence: 99%